Disruption - West, Traci C. (Journal of the Society of Christian Ethics, 2022)
To examine the institutional ethics of the church there must be a focus on how the mutually reinforcing interplay of cultural and political values of white supremacy and heteropatriarchy are so effectively perpetuated by Christians through their church bodies. Analysis of this institutional process includes an illustration from the United Methodist Church 2019 quadrennial global assembly and a moment of LGBTQI protest against the Church's enactment of the "traditional plan" banning equality across sexual orientations and gender identities by limiting ordination and full access to pastoral care to cisgender heterosexuals. A transformative vision of institutional ethics of the church requires disruption of the church's commitment to preserving social domination.